Chinese literature students’ attitudes toward EFL learning at an indonesian university - Gabriel, Rafil Achmad; Inayati, Dian ((JELE) Journal Of English Language and Education, 2018)
Considering the importance of attitudes, this study was conducted to identify the attitudes of Chinese Literature Students toward learning English, which is divided into three specific aspects namely: cognitive, affective, and conative. 91 Chinese Literature Students at a University in Indonesia were chosen as the research participants. Using survey design to achieve the objectives of the study, 91 questionnaire sheets were administered to the participants. It was found that the participants have positive attitudes based on three aspects: mean score of 3.73 (74.59%) for cognitive, 3.40 (68%) for affective, and 3.61 (72%) for conative aspects. In terms of attitudes level, 16 (18%) students were low, 56 (62%) were high, and 19 (21%) students were very high. Based on the findings, it can be concluded that Chinese Literature students have positive attitudes towards EFL learning with mean score of 3.58 (72%). Some suggestions are provided regarding the finding and discussion of this research for Chinese Literature students, English teachers/lecturers, curriculum developers, and for future researchers.